The Influence of Training, Competency and Individual Characteristics on the Performance of Tapin District Health Service Employees - Kadir, Abdul; Melania; Jayen, Fredy; Amrulloh, Rifqi; Ari Supriyadi, Agus (Universitas Hang Tuah, 2024)
The aim of this research is to test and analyze the partial and simultaneous influence of training, competency, and individual characteristics on the performance of employees in Tapin District Health Service. This explanatory research aims to explain the relationship, differences, or influence of the variabels training, competency, and individual characteristics on employee performance in Tapin District Health Service. The study population consisted of 96 employees from Tapin District Health Service. The sampling technique used in this research is a saturated sample, which means that the entire population of 96 employees was included in the sample. The research results show that: 1) Simultaneously, training, competency, and individual characteristics have a significant effect on the performance of employees in Tapin District Health Service. 2) Partially, training, competency, and individual characteristics have a significant effect on employee performance in Tapin District Health Service. 3) The variabel that has the most dominant influence on employee performance in Tapin District Health Service is competency.